A Review of Purpose, Benefits, Impediments and Structure of Environmental Management System (EMS) - A. P., Puvanasvaran; M. R., Muhamad; S.T. Kerk, Robert (INSInet Publication, 2010)
The ISO 14001 EMS has been designed to introduce environmental improvement into every aspect of a company’s operations, offers an organized approach to manage environmental issues and it has now become administrative tool towards corporate environmental management.First introduced in 1996 including Malaysia. According to literature review there can be benefits that firms gain by adopting ISO 14001 and so on and so forth. There present information regarding ISO 14001 standard facts promoting adoption base from within firms such as those from Malaysia context.ISO 14001 certification is voluntary, adoption is depend on aspirations of the companies and the external drivers. This study focuses on the internal and external factors that several literatures indicate play significant role in determining adoption of ISO 14001. In Malaysia, the factor such as role of top management, perceived benefit, motivation, market orientation, resource availability, regulatory concerns and organizational culture is choose as independent variables. The adoption of ISO 14001 has been relatively slow outside of Africa/West Asia, value to approximately three percent (3.02 percent).